Aminated chitosan-regulated sodium/potassium co-doped poly(heptazine imide)@cellulose aerogel: achieving efficient adsorption and photocatalytic degradation of dyes and antibiotics - Long Yang; Cong Yang; Lei Xu; Feng Wang; Guorong Zhao; Haiyang Guo; Dongyu Wei; Lianpeng Zhang; Li Liu; Guanben Du (Desalination, 2026)

TFR2 p.A75V mutation aggravates liver iron overload in alcoholic liver disease via ERK pathway - Chao Xie; Yingying Liu; Xiaofan Wang; Long Huang; Xiaoming Wang; Wei Zhang; Lina Wu; Tianhui Liu; Ping Wang; Lin Liu; Xu Fan; Jidong Jia; et al. (Journal of Molecular Medicine, 2026)

A novel benefit-oriented multi-objective optimization framework for efficiency, NOx, and H2S in coal-fired boilers - Cong Wang; Yiqing Yang; Bowen Lin; Jiaqi Ma; Jun Xu; Kai Xu; Long Jiang; Sheng Su; Song Hu; Jun Xiang (Fuel, 2026)

From serpentinization to carbonation: Petrological and geochemical constraints from an ophiolitic reaction profile - Hong-Da Zheng; Qing Xiong; Xiang Zhou; Biao Chang; Hong-Kun Dai; Hong-Zhu Cai; Li Wang; Yi-Cong Li; Long-Fei Xue; Ming Chen; Jian-Ping Zheng (Chemical Geology, 2026)

Anchoring MoOx nanodots in N-doped porous carbon via a biomimetic strategy: enhanced supercapacitor performance - Li Li; Shou-Cheng Jiao; Chang-Wang Shao; Yu-Man Li; Long-Yu Zhang; Xing-Shun Cong; Xian-Yong Wei; Dan Mu (Fuel, 2026)

Retraction notice to “Adsorption and photodegradation of micropollutant in wastewater by photocatalyst TiO2/rice husk biochar” [Environ. Res. 236 (2023) 116789] - Doan Van Thuan; Thi Thu Hien Chu; Ha Do Thi Thanh; Minh Vien Le; Hoang Long Ngo; Cong Lap Le; Huong Pham Thi (Environmental Research, 2026)

Quantum reinforcement learning for dynamic multi-objective energy management in community microgrids - Yan Gu; Huiru Yan; Qingle Wang; Cong Liu; Cheng Liu; Long Cheng (Energy and Buildings, 2026)

Printed PEDOT:PSS/Ti3C2Tx MXene composite transistor biosensor enables stable low-voltage detection of aflatoxin B1 in complex matrices - Gajanan A. Bodkhe; Subramanian Siva; Chenhao Cong; Ian John L. Castro; Long Ma; Se Hyun Kim; Myunghee Kim (Chemical Engineering Journal, 2026)

Biochar-based active capping for heavy metal-contaminated sediments: mechanistic evaluation and diffusion-adsorption modeling of long-term performance - Ying Hou; Mingming Wang; Cong Yan; Wu Xiao; Xiongzhi Long; Yi Wen; Xiaojing Zhao; Hongkai Zhang; Qi Zhang; Hao Xue (Journal of Soils and Sediments, 2026)

Effects of circumferential and streamwise micro-groove arrangements on the hydrodynamic and acoustic performance of a pump-jet propulsor - Chao Wang; Yu Zhao; Cong Sun; Lian-Zhou Wang; Yu-Long Feng (Ocean Engineering, 2026)

Experimental study on the co-combustion characteristics and Cl/N pollutants emissions of the organic waste liquid blended with pulverized coal - Long Yang; Zewu Zhang; Xiaojian Zha; Cong Luo; Wen Chen; Xiaoshan Li; Feixiang Li; Liqi Zhang (Journal of Environmental Chemical Engineering, 2026)

Transfer learning model for coal lower heating value prediction with improved applicability to cross-sample datasets - Jiaqi Ma; Jun Xu; Cong Wang; Bowen Lin; Long Jiang; Kai Xu; Yi Wang; Sheng Su; Song Hu; Jun Xiang (International Journal of Coal Geology, 2026)

Smart autologous plasma-ICG self-assembled carriers prolong half-life of growth factors and enhance antibacterial effect for periodontitis therapy - Hailun Zhou; Jun Zhou; Xiaoqi Wang; Li Tang; Cong Liu; Chunyun Liang; Hejia Qin; Shufang Zhuo; Ao Long; Fengyuan Zhou; Lu Liu; Wenjin Chen; et al. (Chemical Engineering Journal, 2026)

A potent human neutralizing antibody targeting the receptor-binding site in the glycoprotein gp350 of Epstein-Barr virus - Qingtai Liang; Qian-Ying Zhu; Xin-Yan Fang; Jing Wei; Yi-En Xu; Yanan Zuo; Guo-Long Bu; Chu Xie; Sisi Shan; Cong Sun; Zheng Liu; Linqi Zhang; et al. (Science China Life Sciences, 2026)

Engineering phosphoribosylpyrophosphate synthetase in Methylobacterium radiotolerans for lettuce growth and quality enhancement - Long-Yu Zhang; Dan-Dan Tian; Zhe Liu; Ming-Ming Zhang; Jing Wu; Shuai-Jie Wang; Song Yang; Cong Zhang; Lu Yao; Ling-Ling Tan (Archives of Microbiology, 2026)

DICP1-A precisely degrades STING-A but not STING-B to suppress IFN expression through the autophagic pathway in gibel carp - Yue Wu; Shun Li; Fan-Xiang Gao; Zhi Li; Rui-Hai Gan; Can Zhang; Xiao-Li Yang; Zhuo-Cong Li; Chu-Jing Zhou; Yang-Yang Wang; Na Xu; Xue-Bing Wang; et al. (Aquaculture, 2026)

Integrated eDNA and conventional surveys of coral reef fishes at submerged banks, shoals, and offshore Islands in Southern Vietnam - Long Van Nguyen; Quang Minh Thai; Dat Xuan Mai; Thinh Cong Tran; My Thao Nguyen-Le; Hong Kim Thi Phan; Ben Xuan Hoang; Ha Viet Dao; Binh Thuy Dang; Oanh Thi Truong; Sang Quang Tran (Regional Studies in Marine Science, 2026)

Slope and grain size control on channel-levee development in mixed turbidite-contourite systems - Long He; Tao Jiang; Man Tang; Dongmei Tian; Licheng Cao; Cong Cheng (Marine Geology, 2026)

Eco-sustainable catalytic production of biomass-derived 5,5′-[oxybis(methylene)]bis-2-furfural and its key downstream chemicals: A comprehensive review - Ngan Nguyen Le; Quang Khai Truong; Thuy Dung Hoang To; Doan Van Thuan; Ngan Tuan Nguyen; Thanh Tung Nguyen; Hoang Long Ngo; Cong Chien Truong (Biomass and Bioenergy, 2026)

Mantle dunites archive multistage melt metasomatism under a fossil slow-ultraslow spreading center: an example from the Tibetan Xigaze ophiolite - Li Wang; Qing Xiong; Hong-Kun Dai; Xiang Zhou; Hong-Da Zheng; Hao-Qin Sun; Yi-Cong Li; Long-Fei Xue; Alessio Sanfilippo; Valentin Basch; Jian-Ping Zheng (Contributions to Mineralogy and Petrology, 2026)

Enhanced nutrient removal and microbial stability in a hybrid membrane bioreactor driven by Chlorella sorokiniana-Bacteria synergism - Thi-Mai-Phuong Nguyen; Phan Nhu Nguyet; Ngo Hoang Long; Phuong-Thao Nguyen; Huu-Viet Nguyen; Cong-Sac Tran; My-Le Du; Masashi Hatamoto; Takahiro Watari; Takashi Yamaguchi (Journal of Water Process Engineering, 2026)

A general framework for designing and assessing sustainable and diversified cropping systems: Bridging knowledge-driven, model-aided, and participatory approaches - Zhengyuan Liang; Bowen Ma; Rui-Peng Yu; Yuewen Huo; Shingirai Mudare; Feiyu Ying; Long Li; Fusuo Zhang; Wen-Feng Cong (Field Crops Research, 2026)

Flexural behavior investigation of RC beams with FRP-reinforced 3D-printed ECC permanent formwork - Long-yu Cong; Fang Zhang; Yong-jiu Qian (Engineering Structures, 2026)

Solidago canadensis alters rhizosphere bacterial communities of Artemisia argyi under warming and nitrogen deposition—invaded rhizospheres become similar to the invader's - Yong-Feng Wang; Yun-Long Zhang; Ying Li; Guang-Qian Ren; Shan-Shan Qi; Bi-Ying Zhao; Zhi-Cong Dai; Dao-Lin Du (Plant and Soil, 2026)

Unlocking a new application of coal and biomass co-ethanolysis: high-performance supercapacitor based on N/O self-doped hierarchical porous carbons - Li Li; Yu-Fan Ren; Chang-Wang Shao; Long-Yu Zhang; Guo-Rong Qi; Xing-Shun Cong; Xian-Yong Wei; Zi-Chun Fan; Xiao-Yu Zhang (Fuel, 2026)

Function and mechanisms of polyethylene glycol-modified sodium acrylate-acrylamide hydrogel for microalgal biomass enrichment and purification - Cong-Cong Tang; Qiao Zhong; Yi Liu; Yong-Qi Cheng; Sheng-Long Chen; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Chemical Engineering Journal, 2026)

Quantitative pollen-vegetation relationships in southern subtropical evergreen broadleaved forests in China and the effects of human disturbance - Qiuchi Wan; Haoxin Ye; Kangyou Huang; Xiangyue Long; Liping Tian; Xiao Zhang; Cong Chen; Yaze Zhang; Kunshan Bao; Zhuo Zheng (Science China Earth Sciences, 2026)

Distinct roles of nitrogen and phosphorus availability in preventing soil organic carbon loss in alfalfa-converted cropland - Xu-Long Zhang; Ge Li; Xiao-Peng Shi; Yang-Yang Zhao; Hai-Long Ma; Wen-Feng Cong; Fusuo Zhang; Feng-Min Li (Agriculture, Ecosystems & Environment, 2026)

Numerical investigation of mixed and natural convection in 19-pin fuel assemblies with wire-wrapped based on the SST k-ω-DHFM model - Yuefeng Guo; Xingkang Su; Guan Wang; Huan Lin; Cong Lin; Long Gu (Annals of Nuclear Energy, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Experimental measurement of laminar burning velocity and reaction kinetics modeling of ammonia-dimethyl ether co-combustion at medium to high pressures - Lu Mingfei; He Chen; Zhang Lin; Long Wuqiang; Wang Yongjian; Dong Pengbo; Yao Chengxi; Cong Lixin; Wang Mengfan; Tian Hua; Wang Yang (Fuel, 2025)

Single-cell transcriptomic profiling of goat milk somatic cells highlights immune heterogeneity and epithelial cell-related networks - Ren Tao; Cong He; Liu Yaolong; Liu Chengli; Ruan Pengcheng; Wang Zixuan; Long Hao-yuan; Simone Ceccobelli; Hu Pengfei; Zeng Yan; Han Yanguo; Sun Yawang; et al. (Food Bioscience, 2025)

Satb2 Ablation Impairs Hippocampus-Based Long-Term Spatial Memory and Short-Term Working Memory and Immediate Early Genes (IEGs)-Mediated Hippocampal Synaptic Plasticity - Ying Li; Qiang-Long You; Sheng-Rong Zhang; Wei-Yuan Huang; Wen-Jun Zou; Wei Jie; Shu-Ji Li; Ji-Hong Liu; Chuang-Ye Lv; Jin Cong; Yu-Ying Hu; Tian-Ming Gao; et al. (Molecular Neurobiology, 2025)

Wetland Loss Offsets Climate Change Benefits on Ecological Security Network in Songnen Plain, Northeast China - Jinyuan Ren; Wenjuan Wang; Lei Wang; Long Fei; Guanghui Shao; Yuhong Li; Shanfeng Xing; Yu Cong (Chinese Geographical Science, 2025)

New insights on co-combustion of organic waste liquid blending with pulverized coal: Synergistic effect on the combustion performance and pollutant control - Long Yang; Zewu Zhang; Feixiang Li; Xiaojian Zha; Wenchao Mao; Cong Luo; Liqi Zhang (Fuel, 2025)

Accelerated aqueous carbonation of phosphorous slag driven by grinding force: The role of depolymerization of glassy network - Jin Yang; Long Wang; Xingyang He; Bohumír Strnadel; Jingyi Zeng; Cong Tian; Senye Liu; Ying Su (Chemical Engineering Journal, 2025)

Novel insights to the synergistic effects of magnetic biochar in anaerobic digestion while treating synthetic organic wastewater for biomethane recovery - Zhang-Wei He; Yuan-Long Jia; Cong-Cong Tang; Ai-Juan Zhou; Wenzong Liu; Yong-Xiang Ren; Aijie Wang; Rong Chen (Chemical Engineering Journal, 2025)

Global Change Alters the Abundance and Community Structure of Arbuscular Mycorrhizal Fungi and Influences Plant Mycorrhizal Benefit - Ai‐Tian Ren; Meng‐Li Wang; He‐Miao Gao; Bede S. Mickan; Long‐Yi Yuan; Si‐Kun Liu; Shao‐Cong Zhang; Lynette K. Abbott; You‐Cai Xiong; Fei Mo (Global Ecology and Biogeography, 2025)
Aims Arbuscular mycorrhizal (AM) fungi play critical roles in ecosystem services and exhibit sensitivity to global change factors (GCFs). However, the interactive effects of multiple GCFs on AM fungal communities, and whether changes in AM fungal communities have a feedback effect on plant–mycorrhizal benefits under global change remain poorly understood. Location Global. Time Period 1990 – 2022. Major Taxa Studied Arbuscular mycorrhizal fungi; arbuscular mycorrhizal plant hosts. Methods We synthesised 1646 observations of arbuscular mycorrhizal (AM) fungal communities from field experiments to evaluate how manipulated GCFs affect their abundance and community structure and to determine the potential consequences for outcomes of plant–mycorrhizal fungal relationships. Results The interactive effects among GCFs were mainly additive rather than synergistic or antagonistic. AM fungal diversity was not consistently sensitive to the individual effects of GCFs; however, a significant shift in community structure occurred under individual or concurrent GCFs. When multiple factors were imposed simultaneously, their negative effect on AM fungal colonisation was strengthened, while their effects on community structure were diminished. Moreover, plant performance was closely linked to changes in abundance and community structure of AM fungi under GCFs. Experimental duration and environmental variables emerged as the most important predictors of AM fungal responses to GCFs. Conclusions Reordering or replacement of AM fungal species has been identified as the key mechanism driving community responses to GCFs. Our study highlights the need to monitor AM fungal community structure and associated functional consequences for plant communities under ongoing global change.

Metagenomic insights into the synergistic properties and mechanisms of sludge microbial communities degrading polystyrene and polypropylene - Ying Zhou; Wei-hua Gu; Jian-feng Bai; Rui-xue Wang; Cheng-long Zhang; Yao-guang Guo; Cong Lu; Shan-ping Chen (Journal of Hazardous Materials, 2025)

Effect of H2O physicochemical properties on NO formation mechanism in NH3 oxy-steam combustion under MILD mode - Xiaojian Zha; Zewu Zhang; Zhenghong Zhao; Long Yang; Wenchao Mao; Fan Wu; Xiaoshan Li; Cong Luo; Liqi Zhang (Fuel, 2025)

Grass carp reovirus VP6 inhibits IFN production by degrading TBK1 through the autophagy pathway - Xiao Xu; Zhuo-Cong Li; Bao-Jie Cui; Can Zhang; Na Xu; Yang-Yang Wang; Dan-Dan Chen; Long-Feng Lu; Shun Li (Fish & Shellfish Immunology, 2025)

Unveiling the seismic attenuation characteristics in the mantle beneath Southeast Asia: Insights into mantle dynamics and tectonic processes - Van-Duong Nguyen; Le-Minh Nguyen; Cong-Nghia Nguyen; Thi-Giang Ha; Vinh-Long Ha; Tien-Hung Nguyen; Quang-Khoi Le (Regional Studies in Marine Science, 2025)

Cyprinid herpesvirus 2 (CyHV-2) ORF67 inhibits IFN expression by competitively obstructing STING phosphorylation - Bao-Jie Cui; Can Zhang; Chu-Jing Zhou; Zhuo-Cong Li; Xiao Xu; Yang-Yang Wang; Dan-Dan Chen; Li Zhou; Long-Feng Lu; Shun Li (Fish & Shellfish Immunology, 2025)

Achieving underpotential Mn deposition chemistry via hydrated eutectic electrolytes for aqueous manganese metal batteries - Quanhuan Yao; Linyang Li; Xue Chen; Shenghui Zhang; He Zhang; Yujie Fu; Cong Tian; Guilong Yan; Anjun Hu; Liujun Cao; Jianping Long (Chemical Engineering Journal, 2025)

Machine learning-based detection of dynamic changes in mangrove forest, Beilun Estuary - Chuqi Long; Zhijun Dai; Xuefei Mei; Xixing Liang; Xuewei Zhang; Yangyang Xi; Riming Wang; Nguyen An Binh; Cong Mai Van; Jinping Cheng (Ocean & Coastal Management, 2025)

Real-time prediction and optimization of NOx emissions using artificial intelligence and online combustion data - Cong Wang; Jun Xu; Kai Xu; Long Jiang; Yi Wang; Sheng Su; Song Hu; Jun Xiang (Fuel, 2025)

Rapid and efficient nitrogen removal by a novel heterotrophic nitrification-aerobic denitrification bacteria Marinobacterium maritimum 5-JS in aquaculture wastewater: Performance and potential applications - Fu-Rong Wang; Shi-Yu Feng; Shuai Liang; Wei-Yu Du; Long-Qi Wang; Yu-Wei Zhang; Jia-Yu Ren; Shuang Gao; Yu-Jie Zhu; Yu-Ting Cong; Li Wang; Jing Gu; et al. (Environmental Research, 2025)

An in-situ gold growth self-catalytic signal amplification system enhanced hollow gold immunochromatography for ultrasensitive detection of p24 antigen in HIV infection - Chuanjiang Ran; Qingjie Zhang; Zhenglin Long; Yuhao Li; Xinyue He; Shengzhou Li; Chen Chen; Cong Cheng; Ying Xu; Wenli Zhang; Wei Guo; Yan Shen (Chemical Engineering Journal, 2025)

Nano-Selenium supplementation Improves Meat Quality, Protein Deposition, and Selenoprotein Gene Expression in Channel Catfish (Ictalurus Punctatus) - Zi Meng Li; Xiao Min Jin; Hui Long Qiu; Wen Hao Xu; Cong Hu; Ke Chen; Jia Qiang Huang; Lian Shun Wang (Biological Trace Element Research, 2025)

A spatiotemporal mixed-enhanced generative adversarial network for radar-based precipitation nowcasting - Long He; Kun Zheng; Huihua Ruan; Shuo Yang; Jinbiao Zhang; Cong Luo; Siyu Tang; Yunlei Yi; Yugang Tian; Jianmei Cheng (Computers & Geosciences, 2025)

Poly (sodium acrylate-acrylamide) hydrogels for enrichment and purification of microalgal biomass in an open system: performance optimization and mechanistic analysis - Cong-Cong Tang; Yong-Qi Cheng; Sheng-Long Chen; Ya-Ru Hu; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Journal of Environmental Management, 2025)

Low-severity fire promote carbon emissions in permafrost peatlands of the Great Khingan Mountains, Northeast China - Guangxin Li; Long Sun; Shengzhen Ji; Xiao Li; Jinxin Cong; Dongxue Han; Guoping Wang; Chuanyu Gao (CATENA, 2025)

Ammonia-methanol laminar combustion experiment and chemical kinetic modeling within broad range of ambient pressure - Mingfei Lu; Wuqiang Long; Zechuan Cui; Pengbo Dong; Lixin Cong; Fuxing Wei; Qingyang Wang; Peng Wang; Dongsheng Dong; Hua Tian (Fuel, 2025)

Numerical investigation of shear effects between seafloor sediment and grousers of deep-sea mining vehicles: a comparison of bionic buffalo hoof grousers and straight grousers - Gen Li; Junlin Zhao; Manhong Li; Xuguang Chen; Zhou Li; Andi Yu; Cong Ding; Zhongtao Wang; Long Yu (Ocean Engineering, 2025)

Mussel-inspired stable and magnetically recyclable Fenton-like catalyst: Preventing iron leaching and accelerating contaminant enrichment via polydopamine modification - Guihua Wang; Bin Peng; Xianhu Long; Xuehui Sun; Yipeng Wang; Ziqi Shi; Cong Nie; Rongfu Huang; Bin Yan (Journal of Water Process Engineering, 2025)

Defective Zn1-xCuxS nanosheet as efficient and durable cathode catalyst for photo-assisted Li-O2 batteries - Cong-Cong Dang; Yi-Ping Liu; Yu-Xin Huang; Xin-Yi Zhang; Zhen-Yi Gu; Jun-Ming Cao; Jin-Zhi Guo; Li-Ming Gao; Xing-Long Wu; Yi-Chun Liu (Chemical Engineering Journal, 2025)

Fe2+ inhibits spring viraemia of carp virus proliferation via ATG14-dependent autophagy - Zhuo-Cong Li; Can Zhang; Na Xu; Xiao Xu; Ke-Jia Han; Chu-Jing Zhou; Yang-Yang Wang; Bao-Jie Cui; Dan-Dan Chen; Long-Feng Lu; Shun Li (Aquaculture, 2025)

Oxidation mechanism of methane fuel blended with dimethyl ether/hydrogen/ammonia via ReaxFF molecular dynamics simulation - Liang Song; Chun-Chen Xu; Jing Ye; Yong Zhang; Fang-Chao Hou; Bo-Cong Chen; Hao-Long Su; Jing Sun (Fuel, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

Effects of rumen metabolite butyric acid on bovine skeletal muscle satellite cells proliferation, apoptosis and transcriptional states during myogenic differentiation - Xiao-Wei Wang; Yan-Ling Ding; Cheng-Long Li; Qing Ma; Yuan-Gang Shi; George E Liu; Cong-Jun Li; Xiao-Long Kang (Domestic Animal Endocrinology, 2025)

Research on layout optimization for propellers of a submarine operation vehicle - Long Xiao; Yu Dai; Cong Xue; Wei-Bin Ma; Cheng-Long Liu (Ocean Engineering, 2024)

Icariin-loaded selenium-gold multi-shell nanocomposites with NIR-II response release to relieve post-damaged bone microenvironment for osteoporosis synergy therapy - Yuqing Li; Xiaotong Feng; Yuwei Li; Qile Song; Naling Long; Xiaoting Fu; Yifan Wang; Yingjiao He; Huiying Yan; Cong Li; Lina Feng; Cundong Fan; et al. (Chemical Engineering Journal, 2024)

Early Cretaceous fayalite-, ferrosilite-, and biotite-bearing rhyolitic porphyries in the Baishuizhai area, South China: Formation by fractional crystallization in the shallow crust - Xiao Liu; Qiang Wang; Xi-Jun Liu; Lin Ma; Derek A. Wyman; Gong-Jian Tang; Wei Dan; Zi-Qi Jiang; Hao Wu; Wan-Long Hu; Jin-Heng Liu; Chuan-Bing Xu; et al. (Lithos, 2024)

Construction of novel Cd-based coordination polymer composite with enhanced solar light driven photocatalysis toward simultaneous chlortetracycline degradation and Cr(VI) reduction - Ye-Xia Li; Cong Ma; Jian Luan; Lei Zhang; Wen-Ze Li; Wen-Long Duan (Journal of Environmental Chemical Engineering, 2024)

Pyrolysis and oxidation mechanisms of ethylene and ethanol blended fuel based on ReaxFF molecular dynamics simulation - Liang Song; Chun-Chen Xu; Jing Ye; Yong Zhang; Biao Chen; Fang-Chao Hou; Bo-Cong Chen; Hao-Long Su; Jing Sun (Fuel, 2024)

Characteristics, sources analysis, and risk assessment of polycyclic aromatic hydrocarbon contamination in surface sediments surrounding tourist island - Hongbing Wang; Jianwei Dong; Junqiao Long; Junyi Jiang; Cong Lin (Marine Pollution Bulletin, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Numerical investigation on the vertical jet fire impinging on the horizontal cylindrical obstacle in a ship engine room: Characteristics and new prediction models of flame length - Shaogang Zhang; Yongqiang Fan; Long Shi; Jiahao Liu; Jianghong Liu; Jinhui Wang; Beihua Cong (Ocean Engineering, 2024)

Determining the onset of summer rainfall over Vietnam using self-organizing maps - Tuan Bui-Minh; Quang-Van Doan; Kim-Cuong Nguyen; Tan Phan-Van; Long Trinh-Tuan; Thanh Cong; Ngoc Trinh-Minh (Climate Dynamics, 2024)

Geotectonic architecture beneath Northern Vietnam revealed by local earthquake tomography combining seismic data from multiple networks - Vinh Long Ha; Hsin-Hua Huang; Bor-Shouh Huang; Le Minh Nguyen; Van Duong Nguyen; Thi Giang Ha; Quang Khoi Le; Quoc Van Dinh; Tu Son Le; Tien Hung Nguyen; Cong Nghia Nguyen; Kyle Ken Smith; et al. (Tectonophysics, 2024)

Modeling and forecasting of coal price based on influencing factors and time series - Cong Wang; Gang Xu; Changliang Sun; Jun Xu; Kai Xu; Long Jiang; Yi Wang; Sheng Su; Song Hu; Jun Xiang (Journal of Cleaner Production, 2024)

A kinematic model for collaborative icebreaker convoy operations in ice-covered waters - Weibin Zhang; Ye Xiao; Cong Liu; Mingyang Zhang; Long Wang; Luqi Feng (Ocean Engineering, 2024)

Assessment of carbon-free fuel ammonia combustion with low methanol blends in reducing GHG emissions including N2O - Mingfei Lu; Wuqiang Long; Fuxing Wei; Dongsheng Dong; Lixin Cong; Pengbo Dong; Hua Tian; Xiaoyu Chen; Shihao Chen; Yongjian Wang; Peng Wang (Journal of Cleaner Production, 2024)

A comparative study on hydrocarbon detection using cepstrum–based methods - Cong Tang; Kang Chen; Qing-Lin He; Long Wen; Qi Ran; Bin Luo; Jing-Hui Chang; Ya-Juan Xue (Journal of Applied Geophysics, 2024)

Engage or retreat? Exploring the determinants of participation in Climate Finance public-private partnerships - Vu Minh Ngo; Huan Huu Nguyen; Hiep Cong Pham; Long Hoang Nguyen (Climatic Change, 2024)

The influence of cardamine hupingshanensis on the microbial community structure of jiuqu and the variation of flavor during the fermentation process of selenium-rich Chinese huangjiu - Jingzhang Geng; Dongqin Li; Siqiao He; Cong Min; Jiangang Long; Shuiyun Yang (International Journal of Gastronomy and Food Science, 2024)

Alterations in Dynamic Functional Connectivity in Patients with Cerebral Small Vessel Disease - Futao Chen; Qian Chen; Yajing Zhu; Cong Long; Jiaming Lu; Yaoxian Jiang; Xin Zhang; Bing Zhang (Translational Stroke Research, 2024)
Cerebral small vessel disease (CSVD) is a common disease that seriously endangers people’s health, and is easily overlooked by both patients and clinicians due to its near-silent onset. Dynamic functional connectivity (DFC) is a new concept focusing on the dynamic features and patterns of brain networks that represents a powerful tool for gaining novel insight into neurological diseases. To assess alterations in DFC in CSVD patients, and the correlation of DFC with cognitive function. We enrolled 35 CSVD patients and 31 normal control subjects (NC). Resting-state functional MRI (rs-fMRI) with a sliding-window approach and k -means clustering based on independent component analysis (ICA) was used to evaluate DFC. The temporal properties of fractional windows and the mean dwell time in each state, as well as the number of transitions between each pair of DFC states, were calculated. Additionally, we assessed the functional connectivity (FC) strength of the dynamic states and the associations of altered neuroimaging measures with cognitive performance. A dynamic analysis of all included subjects suggested four distinct functional connectivity states. Compared with the NC group, the CSVD group had more fractional windows and longer mean dwell times in state 4 characterized by sparse FC both inter-network and intra-networks. Additionally, the CSVD group had a reduced number of windows and shorter mean dwell times compared to the NC group in state 3 characterized by highly positive FC between the somatomotor and visual networks, and negative FC in the basal ganglia and somatomotor and visual networks. The number of transitions between state 2 and state 3 and between state 3 and state 4 was significantly reduced in the CSVD group compared to the NC group. Moreover, there was a significant difference in the FC strength between the two groups, and the altered temporal properties of DFC were significantly related to cognitive performance. Our study indicated that CSVD is characterized by altered temporal properties in DFC that may be sensitive neuroimaging biomarkers for early disease identification. Further study of DFC alterations could help us to better understand the progressive dysfunction of networks in CSVD patients.

Spatiotemporal variations, sources, and atmospheric transformation potential of volatile organic compounds in an industrial zone based on high-resolution measurements in three plants - Jin-Long Mai; Xing-Cong Cai; De-Yao Luo; Yuan Zeng; Yu-Feng Guan; Wei Gao; She-Jun Chen (Science of The Total Environment, 2024)

The FAK/occludin/ZO-1 complex is critical for cadmium-induced testicular damage by disruption of the integrity of the blood-testis barrier in chickens - Xiao-Wei Li; Sheng Li; Yu Yang; Milton Talukder; Xiang-Wen Xu; Chen-Xi Li; Cong Zhang; Xue-Nan Li; Jin-Long Li (Journal of Hazardous Materials, 2024)

Role of phosphate in microalgal-bacterial symbiosis system treating wastewater containing heavy metals - Cong-Cong Tang; Ya-Ru Hu; Min Zhang; Sheng-Long Chen; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Environmental Pollution, 2024)

Occurrence, distribution, and risk assessment of antibiotics in a typical aquaculture area around the Dongzhai Harbor mangrove forest on Hainan Island - Tuan-Tuan Wang; Shuai Shao; Shi-Di Fan; Wang-Qing Tang; Jiang-Wei Miao; Sai Wang; Xiao-Cong Cao; Chuan Liu; Guang-Guo Ying; Zhong-Bing Chen; Hai-Long Zhou; Xiao-Ping Diao; et al. (Science of The Total Environment, 2024)

Co-combustion characteristics and reaction mechanism of coal slime and sewage sludge using a novel multilateral double volumetric parallel model and dendrite neural network - Peng Ling; Mohamed E. Mostafa; Kai Xu; Cong Wang; Haoran Qing; Yan Jin; Jun Xu; Long Jiang; Yi Wang; Sheng Su; Song Hu; Jun Xiang (Journal of Environmental Chemical Engineering, 2024)

Cognitive Deficits and Alzheimer’s Disease-Like Pathologies in the Aged Chinese Tree Shrew - Hongli Li; Bo-Lin Xiang; Xiao Li; Cong Li; Yu Li; Ying Miao; Guo-Lan Ma; Yu-Hua Ma; Jia-Qi Chen; Qing-Yu Zhang; Long-Bao Lv; Ping Zheng; et al. (Molecular Neurobiology, 2024)

Profiling dynamics of the Southeast Asia's largest lake, Tonle Sap Lake - Wenting Jiang; Zhijun Dai; Xuefei Mei; Chuqi Long; Nguyen An Binh; Cong Mai Van; Jinping Cheng (Science of The Total Environment, 2024)

Glycerol dialkyl glycerol tetraethers in surficial marine sediments across shelf-to-basin depth transects in the East China Sea: Their sources and potential as sea water temperature proxies - Xi Mei; Zhongbo Wang; Wei Xiong; Yong Zhang; Yanguang Dou; Long Huang; Beibei Mi; Zhonglei Wang; Jingyi Cong (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Phosphorus recovery from fertilizer industrial wastewaters using bittern: Influence of wastewater composition and pH on struvite formation - Minh-Vien Le; Tran Huynh Thanh Duy; Bao-Trong Dang; Van Hoang Luan; Ngoc-Diem-Trinh Huynh; Nguyen Quang Long; Le Cong Nhat Phuong (Bioresource Technology Reports, 2024)

Aboveground wheat biomass estimation from a low-altitude UAV platform based on multimodal remote sensing data fusion with the introduction of terrain factors - Shao-Hua Zhang; Li He; Jian-Zhao Duan; Shao-Long Zang; Tian-Cong Yang; U. R. S. Schulthess; Tian-Cai Guo; Chen-Yang Wang; Wei Feng (Precision Agriculture, 2024)

SnS2/MWNTs/sponge electrode combined with plasma dielectric barrier discharge catalytic system: CO2 reduction and pollutant degradation - Yiping Shen; Yupei Long; Fangying Li; Yun Ji; Yanqing Cong; Boqiong Jiang; Yi Zhang (Chemosphere, 2023)

ZIC2 accelerates growth and stemness in gastric cancer through the Wnt/β-catenin pathway - Ying Yu; Chao Tan; Li Ding; Zhen Zhu; Gong Zhang; Cong Long (Tissue and Cell, 2023)

Adverse effects of thiamethoxam on the behavior, biochemical responses, hepatopancreas health, transcriptome and intestinal flora of juvenile Chinese mitten crab (Eriocheir sinensis) - Yiwen Yang; Cong Zhang; Xiaodan Wang; Qiuran Yu; Long He; Xinyu Cai; Erchao Li; Chuanjie Qin; Jianguang Qin; Liqiao Chen (Chemosphere, 2023)

RETRACTED: Adsorption and photodegradation of micropollutant in wastewater by photocatalyst TiO2/rice husk biochar - Doan Van Thuan; Thi Thu Hien Chu; Ha Do Thi Thanh; Minh Vien Le; Hoang Long Ngo; Cong Lap Le; Huong Pham Thi (Environmental Research, 2023)

Revealing mechanisms of triclosan on the removal and distribution of nitrogen and phosphorus in microalgal-bacterial symbiosis system - Sheng-Long Chen; Tian-Yang Wang; Cong-Cong Tang; Rong Wang; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Environmental Pollution, 2023)

Reliability analysis of core power optimization control using Kalman filter for accelerator driven system based on reconfigurable computing - Jin-Yang Li; Huan Lin; Long Gu; You-Peng Zhang; Jun-Liang Du; Yong-Quan Wang; Cong Lin; Xing-Chen Zhou; Tian Wang (Annals of Nuclear Energy, 2023)

Corrigendum to “Ca2+ plays an antiviral role by increasing p53 expression to achieve protection against spring viraemia of carp virus infection” [Fish Shellfish Immunol. 102 (2020) 449–459/455] - Long-Feng Lu; Xiao-Yu Zhou; Can Zhang; Zhuo-Cong Li; Dan-Dan Chen; Yong-An Zhang; Shun Li (Fish & Shellfish Immunology, 2023)

Involvement of the heat shock response (HSR) regulatory pathway in cadmium-elicited cerebral damage - Milton Talukder; Shao-Shuai Bi; Mei-Wei Lv; Jing Ge; Cong Zhang; Jin-Long Li (Environmental Science and Pollution Research, 2023)

Unveiling the role of biochar in simultaneous removal of hexavalent chromium and trichloroethylene by biochar supported nanoscale zero-valent iron - Linbo Qian; Ying Long; Hangyu Li; Zifei Wei; Cong Liang; Renlan Liu; Mengfang Chen (Science of The Total Environment, 2023)

Effects of AAEMs on the char heterogeneous structure evolution during Zhundong coal pyrolysis: Insights from micro-Raman spectroscopy - Qichen He; Jun Xu; Xu Jiang; Cong Wang; Ming Jiang; Yufan Wei; Long Jiang; Kai Xu; Yi Wang; Sheng Su; Song Hu; Jun Xiang (Fuel, 2023)

Seafloor depth mapping of central Vietnam’s sea area and its surrounding using gravity anomaly data and gravity geological method - Nguyen Van Sang; Khuong Van Long; Tran Tuan Dung; Lam Van Nguyen; Bui Cong Que; Do Van Mong; Bui Dang Quang; Ole Baltazar Andersen; Rene Forsberg; Dieu Tien Bui (Advances in Space Research, 2023)

Identification and functional study of detoxification-related genes in response to tolfenpyrad stress in Glyphodes pyloalis Walker (Lepidoptera: Pyralidae) - Xin Pan; Jian-Hao Ding; Shuai-Qi Zhao; Hui-Cong Shi; Wang-Long Miao; Fu-An Wu; Sheng Sheng; Wei-Hong Zhou (Pesticide Biochemistry and Physiology, 2023)

Parametric optimization of vortex generator configuration for flow control in an intake duct for waterjet propulsion - Liu Chen; Ying-Ying Zhou; Cong-Lei Huang; Zong-Long Wang; Ren Dai (Ocean Engineering, 2023)

Coastal acoustic tomography system for monitoring transect suspended sediment discharge of Yangtze river - Cong Xiao; Xiao-Hua Zhu; Chuanzheng Zhang; Ze-Nan Zhu; Yun Long Ma; Ji Wen Zhong; Li Xin Wei (Journal of Hydrology, 2023)

A novel water disinfection method via cuprous ion generation in a copper ferrite/sulfite system and associated mechanism - Lu Qin; Dongqi Wang; Cong Liu; Guodong Chai; Mingliang Fang; Jiake Li; Hui Wang; Zhe Wang; Haiyu Meng; Xing Zheng; Mengbo Huang; Yi Xiao; et al. (Journal of Water Process Engineering, 2023)

Preparation of Cu-Doped Bicontinuous Catalyst and the Performance in Non-thermal Plasma Co-catalytic Degradation of H2S - Sheng nan Chen; Ying jun Gao; Hao Ming; Long long Ren; Cong Geng; Xin jun Shen; Chen guang Shen; Yin yan Guan; Wei chun Gao (Water, Air, & Soil Pollution, 2023)

Protective effects of electroacupuncture on polycystic ovary syndrome in rats: Down-regulating Alas2 to inhibit apoptosis, oxidative stress, and mitochondrial dysfunction in ovarian granulosa cells - Jing Cong; Mubai Li; Yu Wang; Hongli Ma; Xinming Yang; Jingshu Gao; Long Wang; Xiaoke Wu (Tissue and Cell, 2023)

Chemical mechanism of ammonia-methanol combustion and chemical reaction kinetics analysis for different methanol blends - Mingfei Lu; Dongsheng Dong; Fuxing Wei; Wuqiang Long; Yongjian Wang; Lixin Cong; Pengbo Dong; Hua Tian; Peng Wang (Fuel, 2023)

Fire plume characteristics of annular pool fire with different cylindrical obstacles in a ship engine room - Shaogang Zhang; Wei Fang; Long Shi; Jiahao Liu; Jianghong Liu; Jinhui Wang; Beihua Cong (Ocean Engineering, 2023)

Dichloroacetic acid and rapamycin synergistically inhibit tumor progression - Huan Chen; Kunming Liang; Cong Hou; Hai-long Piao (Journal of Zhejiang University-SCIENCE B, 2023)

Experimental study on temperature attenuation of smoke flow driven by dual fire sources in a tunnel - Kun He; Long Shi; Shaogang Zhang; Wei Cong; Hui Yang; Xudong Cheng (Tunnelling and Underground Space Technology, 2023)

Southern extension of raccoon dog Nyctereutes procyonoides (Mammalia: Carnivora: Canidae) range in Vietnam with comments on its conservation status in the country - Thong Van Pham; Mai Thi Trinh; Russell J. Gray; Long Nhat Cao; Tan Van Nguyen; Manh Van Nguyen; Tuan Cong Anh Vo; Nga Thi Nguyen; Long Thi Nguyen; Cuong Xuan Tran; Daniel Willcox; Thai Nguyen Van (European Journal of Wildlife Research, 2023)

Constitutive model for Ya’an mudstone based on mesoscopic breakage mechanism - Yun-yong He; Cong Chen; Fu-ming Wang; Cheng-chao Guo; Bo Xiang; Di Yu; En-long Liu; Chun Ding (Journal of Mountain Science, 2023)

Integrated dual-channel electrochemical immunosensor for early diagnosis and monitoring of periodontitis by detecting multiple biomarkers in saliva - Wei Zhang; Juanrui Du; Kun Wang; Yige Li; Cong Chen; Long Yang; Zitong Kan; Biao Dong; Lin Wang; Lin Xu (Analytica Chimica Acta, 2023)

Controlling factors on the charging process of oil and gas in the eastern main sub-sag of the Baiyun Sag, Zhujiang River (Pearl River) Mouth Basin - Cong Chen; Xiangtao Zhang; Guangrong Peng; Zulie Long; Baojun Liu; Xudong Wang; Puqiang Zhai; Bo Zhang (Acta Oceanologica Sinica, 2023)

ZnCo2O4 composite catalyst accelerated removal of phenylic contaminants containing of Cr(VI) in dielectric barrier discharge reactor: Process and mechanism study - Tao Qiang; Jutao Nie; Yupei Long; Wenbin Wang; Ruizhang Xie; Run Wang; Yanqing Cong; Yi Zhang (Chemosphere, 2023)

Risks of applying mobilising agents for remediation of arsenic-contaminated soils: Effects of dithionite–EDTA and citric acid on arsenic fractionation, leachability, oral bioavailability/bioaccessibility and speciation - Xiao-Chen Chen; Cong-Cong Yao; Ao Wang; Zeng-Di Zhang; Long-Zhao Chen; Jian-Yu Zhang; Xian-Hua Liu; Hong-Bo Li (Journal of Hazardous Materials, 2023)

Secular trend in water discharge transport in the Lower Mekong River-delta: Effects of multiple anthropogenic stressors, rainfall, and tropical cyclones - Runan Tang; Zhijun Dai; Xuefei Mei; Xiaoyan Zhou; Chuqi Long; Cong Mai Van (Estuarine, Coastal and Shelf Science, 2023)

Experimental study on temperature characteristics in a subway train carriage with lateral openings in a longitudinally ventilated tunnel - Wei Cong; Kun He; Hui Yang; Long Shi; Xudong Cheng (Tunnelling and Underground Space Technology, 2023)

Digital Transformation of Packaged Reverse Osmosis Plants for Industrial and Sewer Mining Applications - Claudio Kohn; Hung Cong Duong; Ngoc Bich Hoang; Long Duc Nghiem (Current Pollution Reports, 2022)

Cerebellar injury induced by cadmium via disrupting the heat-shock response - Shao-Shuai Bi; Milton Talukder; Xue-Tong Sun; Mei-Wei Lv; Jing Ge; Cong Zhang; Jin-Long Li (Environmental Science and Pollution Research, 2022)

Cadmium Through Disturbing MTF1-Mediated Metal Response Induced Cerebellar Injury - Shao-Shuai Bi; Milton Talukder; Hai-Tao Jin; Mei-Wei Lv; Jing Ge; Cong Zhang; Jin-Long Li (Neurotoxicity Research, 2022)

Assessment of pilot direct contact membrane distillation regeneration of lithium chloride solution in liquid desiccant air-conditioning systems using computer simulation - Hung Cong Duong; Long Duc Nghiem; Ashley Joy Ansari; Thao Dinh Vu; Khai Manh Nguyen (Environmental Science and Pollution Research, 2022)

Effects of inorganic alkalis and organic anions in biochars on acidic paddy soil resistance to acidification - Xian He; Hai-long Lu; Cong-min Wu; Ren-kou Xu (Journal of Soils and Sediments, 2022)

The first complete chloroplast genome of Vicatia thibetica de Boiss.: genome features, comparative analysis, and phylogenetic relationships - Yun-hui Guan; Wen-wen Liu; Bao-zhong Duan; Hai-zhu Zhang; Xu-bing Chen; Ying Wang; Cong-long Xia (Physiology and Molecular Biology of Plants, 2022)

SKI knockdown suppresses apoptosis and extracellular matrix degradation of nucleus pulposus cells via inhibition of the Wnt/β-catenin pathway and ameliorates disc degeneration - Zuo-long Wu; Ya-jun Chen; Guang-zhi Zhang; Qi-qi Xie; Ke-ping Wang; Xin Yang; Tai-Cong Liu; Zhi-qiang Wang; Guang-hai Zhao; Hai-Hong Zhang (Apoptosis, 2022)

Characterization and diversity of magnetotactic bacteria from sediments of Caroline Seamount in the Western Pacific Ocean - Kaixuan Cui; Wenyan Zhang; Jia Liu; Cong Xu; Yicong Zhao; Si Chen; Hongmiao Pan; Tian Xiao; Long-Fei Wu (Journal of Oceanology and Limnology, 2021)

Correction to: HOXA11‑AS promotes the migration and invasion of hepatocellular carcinoma cells by inhibiting miR‑124 expression by binding to EZH2 - Wen‑long Zhang; Ya‑nan Zhao; Zhang‑zhen Shi; Gui‑ying Gu; Dan Cong; Chen Wei; Yuan‑song Bai (Human Cell, 2021)

Complete genome analysis of the newly isolated Shigella sonnei phage vB_SsoM_Z31 - Bingdong Wei; Cong Cong; Lichun Zhang; Lin Zheng; Long Chen; Wei Yu; Yongping Xu (Archives of Virology, 2021)

Effect of first-stage aeration on treatment of domestic sewage in different hybrid constructed wetlands - Fei-Long Yan; Yi Wang; Wen-Huai Wang; Heng Zhang; Yu-Cong Zheng; Xiao-Mei Kou; Shi-Zhang Wu; Tian Shao (Environmental Science and Pollution Research, 2021)

Design and Characterization of a Novel Hybrid Antimicrobial Peptide OM19R Based on Oncocin and MDAP-2 - Lei Liu; Jie Liu; Qi Cui; Bo-Yan Jia; Zhi-Hua Pei; Kokou Ayefounin Odah; Yi-Ming Wang; Wen-Long Dong; Ling-Cong Kong; Hong-Xia Ma (International Journal of Peptide Research and Therapeutics, 2020)

Low Serum Uric Acid Levels Promote Hypertensive Intracerebral Hemorrhage by Disrupting the Smooth Muscle Cell-Elastin Contractile Unit and Upregulating the Erk1/2-MMP Axis - Ning Xiao; Tian-long Liu; Hao Li; Hao-chen Xu; Jing Ge; Hong-yan Wen; Cong-xia Bai; Li Song; Ying-ying Sun; Yin-hui Zhang; Ru-tai Hui; Wei-hua Song; et al. (Translational Stroke Research, 2020)

Effects of dietary Lactobacillus plantarum C20015 on growth, immunity, and disease resistance in koi carp - Hai-peng Zhang; Wen-long Dong; Long Chen; Yi-ming Wang; Inam Muhammad; An-qi Ju; Xiao-feng Shan; Hong-xia Ma; Ling-cong Kong (Aquaculture International, 2020)

Membrane Distillation for Strategic Water Treatment Applications: Opportunities, Challenges, and Current Status - Hung Cong Duong; Ashley Joy Ansari; Ruth Habte Hailemariam; Yun Chul Woo; Thao Manh Pham; Lan Thi Ngo; Duong Thanh Dao; Long Duc Nghiem (Current Pollution Reports, 2020)

A novel putative betapartitivirus isolated from the plant-pathogenic fungus Rhizoctonia solani - Yi Chen; Jia En Su; Xi Yun Qin; Zhi Yong Fan; Xiao Hai Zhang; Qing Yu; Zhen Yuan Xia; Cong Ming Zou; Gao Kun Zhao; Zhong Long Lin (Archives of Virology, 2020)

Isolation, Identification, and Characterization of a Novel Bacteriocin Produced by Brevibacillus laterosporus DS-3 Against Methicillin-Resistant Staphylococcus aureus (MRSA) - Kokou Ayefounin Odah; Wen-Long Dong; Liu Lei; Luke Atiewin Atiah; Yi-ming Wang; Ling-Cong Kong; Hong-Xia Ma (International Journal of Peptide Research and Therapeutics, 2020)

Study on the Treatment of Nickel-Contaminated Soil Using Calcium Oxide - Zhen-li Xiang; Huan-fang Gao; Huan Yan; Ya-ling Li; Zhi-long Diao; En-zhi Zhang; Cong Li; Yuan-cheng Cao (Water, Air, & Soil Pollution, 2020)

Paleoproterozoic A-type granite from the southwestern margin of the North China block: high temperature melting of tonalitic crust in extensional setting - Xing-Ying Wang; Jiang-Feng Qin; Shao-Cong Lai; Xiao-Ping Long; Yin-Juan Ju; Ze-Zhong Zhang; Ren-Zhi Zhu (International Geology Review, 2020)

Mercury bioaccumulation in zooplankton and its relationship with eutrophication in the waters in the karst region of Guizhou Province, Southwest China - Cong Yao; Tianrong He; Yiyuan Xu; Shu Ran; Xiaoli Qian; Shengxing Long (Environmental Science and Pollution Research, 2020)

Membrane Processes for the Regeneration of Liquid Desiccant Solution for Air Conditioning - Hung Cong Duong; Ashley Joy Ansari; Long Duc Nghiem; Hai Thuong Cao; Thao Dinh Vu; Thao Phuong Nguyen (Current Pollution Reports, 2019)

HOXA11-AS promotes the migration and invasion of hepatocellular carcinoma cells by inhibiting miR-124 expression by binding to EZH2 - Wen-long Zhang; Ya-nan Zhao; Zhang-zhen Shi; Gui-ying Gu; Dan Cong; Chen Wei; Yuan-song Bai (Human Cell, 2019)

Ottowia flava sp. nov., isolated from fish intestines - Song-Biao Shi; Gui-Ding Li; Li-Fang Yang; Cong Liu; Ming-Guo Jiang; Qin-Yuan Li; Jia-Fa Wu; Kun Zhang; Long-Qian Jiang; Nai-Kun Shen; Cheng-Lin Jiang; Yi Jiang (Antonie van Leeuwenhoek, 2019)

Antimicrobial resistance and presence of virulence factor genes in Trueperella pyogenes isolated from pig lungs with pneumonia - Wen-Long Dong; Lei Liu; Kokou Ayefounin Odah; Luke Atiewin Atiah; Yun-Hang Gao; Ling-Cong Kong; Hong-Xia Ma (Tropical Animal Health and Production, 2019)

Archaeal community structure in sediments from a seamount in the Mariana Volcanic Arc - Wenyan Zhang; Jia Liu; Yi Dong; Xuegang Li; Cong Xu; Tian Xiao; Hongmiao Pan; Long-Fei Wu (Journal of Oceanology and Limnology, 2019)

Antimicrobial susceptibility and molecular typing of Pasteurella multocida isolated from six provinces in China - Ling-Cong Kong; Zi Wang; Yi-Ming Wang; Wen-Long Dong; Bo-Yan Jia; Duo Gao; Xiu-Yun Jiang; Hong-Xia Ma (Tropical Animal Health and Production, 2019)

Interactions between polycyclic aromatic hydrocarbons and epoxide hydrolase 1 play roles in asthma - Qihua Wang; Xijin Xu; Xiaowei Cong; Zhijun Zeng; Long Xu; Xia Huo (Environmental Geochemistry and Health, 2019)

Low Carbon Desalination by Innovative Membrane Materials and Processes - Hung Cong Duong; Ashley J. Ansari; Long D. Nghiem; Thao M. Pham; Thang D. Pham (Current Pollution Reports, 2018)

Origin of Early Cretaceous Guandian adakitic pluton in central eastern China: partial melting of delaminated lower continental crust triggered by ridge subduction - Ze-Bin Luo; Shuo Xue; Li-Peng Zhang; He Li; Cong-Ying Li; Hong Zhang; Yu-Long Liu; Ming-Xing Ling; Weidong Sun (International Geology Review, 2018)

Dual functional adsorbent/catalyst of nano-gold/metal oxides supported on carbon grain for low-temperature removal of toluene in the presence of water vapor - Nguyen Thanh Minh; Le Duc Thanh; Bien Cong Trung; Ngo Thanh An; Nguyen Quang Long (Clean Technologies and Environmental Policy, 2018)

Balanochalcone, a new chalcone from Balanophora laxiflora Hemsl. - Dang Ngoc Quang; Tran Cong So; Nguyen Thi Phuong Thanh; Le Thi Phuong Hoa; Pham Huu Dien; Truong Minh Luong; Nguyen Quang Tung; Le Duc Long; Tran Duc Dai; Nguyen Quyet Tien (Natural Product Research, 2018)

Improved antifouling properties of photobioreactors by surface grafted sulfobetaine polymers - Dongwei Wang; Xia Wu; Lixia Long; Xubo Yuan; Qinghua Zhang; Shengzhang Xue; Shumei Wen; Chenghu Yan; Jianming Wang; Wei Cong (Biofouling, 2017)

Anti-complementary constituents of Viola kunawarensis - Hui Wang; Wen-Li Cong; Ze-long Fu; Dao-Feng Chen; Qi Wang (Natural Product Research, 2017)

Temperature drop and the risk of asthma: a systematic review and meta-analysis - Xiaowei Cong; Xijin Xu; Yuling Zhang; Qihua Wang; Long Xu; Xia Huo (Environmental Science and Pollution Research, 2017)

A Novel miRNA Sponge Form Efficiently Inhibits the Activity of miR393 and Enhances the Salt Tolerance and ABA Insensitivity in Arabidopsis thaliana - Ruicai Long; Mingna Li; Xiao Li; Yanli Gao; Tiejun Zhang; Yan Sun; Junmei Kang; Tenghua Wang; Lili Cong; Qingchuan Yang (Plant Molecular Biology Reporter, 2017)

Metformin Improves Functional Recovery After Spinal Cord Injury via Autophagy Flux Stimulation - Di Zhang; Jun Xuan; Bin-bin Zheng; Yu-long Zhou; Yan Lin; Yao-sen Wu; Yi-fei Zhou; Yi-xing Huang; Quan Wang; Li-yan Shen; Cong Mao; Yan Wu; et al. (Molecular Neurobiology, 2017)

Characterization of uncultivated magnetotactic bacteria from the sediments of Yuehu Lake, China - Haijian Du; Rui Zhang; Wenyan Zhang; Cong Xu; Yiran Chen; Hongmiao Pan; Ke Zhou; Long-fei Wu; Tian Xiao (Acta Oceanologica Sinica, 2017)

Tumor Targeting Synergistic Drug Delivery by Self-Assembled Hybrid Nanovesicles to Overcome Drug Resistance - Meng-Qing Gong; Cong Wu; Xiao-Yan He; Jing-Yi Zong; Jin-Long Wu; Ren-Xi Zhuo; Si-Xue Cheng (Pharmaceutical Research, 2017)

Dietary Selenium Status Regulates the Transcriptions of Selenoproteome and Activities of Selenoenzymes in Chicken Kidney at Low or Super-nutritional Levels - Jing-Xiu Xu; Cong Zhang; Chang-Yu Cao; Shi-Yong Zhu; Hui Li; Yan-Chun Sun; Jin-Long Li (Biological Trace Element Research, 2016)

N2O emissions from banana plantations in tropical China as affected by the application rates of urea and a urease/nitrification inhibitor - Tongbin Zhu; Junhua Zhang; Ping Huang; Long Suo; Cong Wang; Weixin Ding; Lei Meng; Kexin Zhou; Zhewei Hu (Biology and Fertility of Soils, 2015)

Isolation and functional characterization of salt-stress induced RCI2-like genes from Medicago sativa and Medicago truncatula - Ruicai Long; Fan Zhang; Zhenyi Li; Mingna Li; Lili Cong; Junmei Kang; Tiejun Zhang; Zhongxiang Zhao; Yan Sun; Qingchuan Yang (Journal of Plant Research, 2015)

Intercropping affects the rate of decomposition of soil organic matter and root litter - Wen-Feng Cong; Ellis Hoffland; Long Li; Bert H. Janssen; Wopke van der Werf (Plant and Soil, 2015)

Intercropping enhances soil carbon and nitrogen - Wen‐Feng Cong; Ellis Hoffland; Long Li; Johan Six; Jian‐Hao Sun; Xing‐Guo Bao; Fu‐Suo Zhang; Wopke Van Der Werf (Global Change Biology, 2015)
Intercropping, the simultaneous cultivation of multiple crop species in a single field, increases aboveground productivity due to species complementarity. We hypothesized that intercrops may have greater belowground productivity than sole crops, and sequester more soil carbon over time due to greater input of root litter. Here, we demonstrate a divergence in soil organic carbon (C) and nitrogen (N) content over 7 years in a field experiment that compared rotational strip intercrop systems and ordinary crop rotations. Soil organic C content in the top 20 cm was 4% ± 1% greater in intercrops than in sole crops, indicating a difference in C sequestration rate between intercrop and sole crop systems of 184 ± 86 kg C ha −1 yr −1 . Soil organic N content in the top 20 cm was 11% ± 1% greater in intercrops than in sole crops, indicating a difference in N sequestration rate between intercrop and sole crop systems of 45 ± 10 kg N ha −1 yr −1 . Total root biomass in intercrops was on average 23% greater than the average root biomass in sole crops, providing a possible mechanism for the observed divergence in soil C sequestration between sole crop and intercrop systems. A lowering of the soil δ 15 N signature suggested that increased biological N fixation and/or reduced gaseous N losses contributed to the increases in soil N in intercrop rotations with faba bean. Increases in soil N in wheat/maize intercrop pointed to contributions from a broader suite of mechanisms for N retention, e.g., complementary N uptake strategies of the intercropped plant species. Our results indicate that soil C sequestration potential of strip intercropping is similar in magnitude to that of currently recommended management practises to conserve organic matter in soil. Intercropping can contribute to multiple agroecosystem services by increased yield, better soil quality and soil C sequestration.

Accurate and Efficient Simulation of Fracture–Matrix Interaction in Shale Gas Reservoirs - Long Cai; Didier-Yu Ding; Cong Wang; Yu-Shu Wu (Transport in Porous Media, 2015)

Regulating phosphoenolpyruvate carboxylase activity by copper-induced expression method and exploring its role of carbon flux distribution in Synechocystis PCC 6803 - Fei Yan; Long Quan; Zhang Wei; Wei Cong (Journal of Applied Phycology, 2015)

Enhanced photo-H2 production by unsaturated flow condition in continuous culture - Cheng-Long Guo; Hong-Xia Cao; Fei-Qiang Guo; Cong-Liang Huang; Huan-Guang Wang; Zhong-Hao Rao (Biotechnology Letters, 2015)

Origin area and migration route: Chloroplast DNA diversity in the arctic-alpine plant Koenigia islandica - Cong Long; YunJiang Min; XiuXia Zhao; ChunLei Yany; Hang Sun; HouYuan Lü; LingYu Tang; ZhongZe Zhou (Science China Earth Sciences, 2014)

Three homologous genes encoding functional ∆8-sphingolipid desaturase in Populus tomentosa - Shu-Fen Li; Guo-Jun Zhang; Ying-Chun Yuan; Cong-Hui Wang; Wu-Jun Gao; Chuan-Liang Deng; Long-Dou Lu; Zan-Min Hu (Genes & Genomics, 2014)

High seroprevalence of Chlamydia infection in sows in Hunan province, subtropical China - Xiao-Xuan Zhang; Run-Cheng Li; Guo-Hua Liu; Wei Cong; Hui-Qun Song; Xing-Long Yu; Xing-Quan Zhu (Tropical Animal Health and Production, 2014)

Shapinggou: the largest Climax-type porphyry Mo deposit in China - Hong Zhang; Cong-Ying Li; Xiao-Yong Yang; Ya-Li Sun; Jiang-Hong Deng; Hua-Ying Liang; Rui-Long Wang; Bo-Hua Wang; Yu-Xian Wang; Wei-Dong Sun (International Geology Review, 2014)

Microbiota Regulates the TLR7 Signaling Pathway Against Respiratory Tract Influenza A Virus Infection - Sha Wu; Zhen-You Jiang; Yi-Fan Sun; Bin Yu; Jia Chen; Cong-Qi Dai; Xian-Lin Wu; Xiao-Long Tang; Xiao-Yin Chen (Current Microbiology, 2013)

Chemical composition and source apportionment of rainwater at Guiyang, SW China - Hong-Wei Xiao; Hua-Yun Xiao; Ai-Min Long; Yan-Li Wang; Cong-Qiang Liu (Journal of Atmospheric Chemistry, 2013)

Characterization and Expression of a Phytochelatin Synthase Gene in Birch-leaf Pear (Pyrus betulaefolia Bunge) - You Hong Chang; Hui Li; Yu Cong; Jing Lin; Bao Long Sheng (Plant Molecular Biology Reporter, 2012)

Genetic analysis of avian paramyxovirus-1 (Newcastle disease virus) isolates obtained from swine populations in China related to commonly utilized commercial vaccine strains - Zhuang Ding; Yan-long Cong; Shuang Chang; Guang-mei Wang; Ze Wang; Quan-peng Zhang; Hao Wu; Yu-zhang Sun (Virus Genes, 2010)

Antigenic variation between Newcastle disease viruses of goose and chicken origin - Zhi-jie Li; Yang Li; Shuang Chang; Zhuang Ding; Lian-zhi Mu; Yan-long Cong (Archives of Virology, 2010)

Swine infection with H9N2 influenza viruses in China in 2004 - Yan-Long Cong; Chun-Feng Wang; Chun-Mei Yan; Jin-Shan Peng; Zhan-Lei Jiang; Jin-Hua Liu (Virus Genes, 2008)

Supplementary data: Assessment of genetic diversity ofLycoris longituba (Amaryllidaceae) detected by RAPDs - Chuan-Liang Deng; Jian Zhou; Wu-Jun Gao; Fu-Cong Sun; Rui-Yun Qin; Long-Dou Lu (Journal of Genetics, 2006)

Cloning of a novel human NHEDC1 (Na+/H+ exchanger like domain containing 1) gene expressed specifically in testis - Guangming Ye; Cong Chen; Dingding Han; Xiabin Xiong; Yahui Kong; Bo Wan; Long Yu (Molecular Biology Reports, 2006)

Rapid Detection of Avian Influenza Virus A and Subtype H5N1 by Single Step Multiplex Reverse Transcription-polymerase Chain Reaction - Hui-Ling Wei; Gui-Rong Bai; Aaron S. Mweene; Ying-Chun Zhou; Yan-Long Cong; Juan Pu; Shuai Wang; Hiroshi Kida; Jin-Hua Liu (Virus Genes, 2006)

Biooxidation of ferrous iron by immobilized Acidithiobacillus ferrooxidans in poly(vinyl alcohol) cryogel carriers - Zhong-er Long; Yunhong Huang; Zhaoling Cai; Wei Cong; Fan Ouyang (Biotechnology Letters, 2003)

Effects of soil fauna on litter decomposition - Xue-ping Zhang; Si-cong Zhang; Chu-long Huang (Chinese Geographical Science, 2001)